ANALISIS PROBABILITAS PENYERAPAN PASAR PUSAT PERBELANJAAN DI KOTA BANDUNG TAHUN 2011 - , Anton Debianto, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Catchment Area Analysis is an important theory to know the probability of a market absorption before we decide to invest in the shopping center property. By this analysis, we will be able to know the shopping custom that people do, we can also calculate the frequency of customerâs visit, and also estimate the potential shopping space demand. This research objects are 6 shopping malls in Bandung City. There are two models that used in this analysis. First, is the model of Huffâs probability, which is used to estimate the probability of customerâs visit of each shopping center in order to know the competition among the malls. The second model is to estimate the shopping malls demand for the space, which is used to know whether the shopping space is enough or not for the customer so we know how to invest. The study result shows that Bandung Supermall has the highest probability in visiting, with 22,35% visitors of Bandung population. By this result, we also know that Bandung city still has a lack of shopping space about 414,717m2.